La polemica antiscettica nel IV libro di Lucrezio. Un’eco antiochea? - The Anti-Sceptical Polemic in Lucretius Book IV: An Echo of Antiochus? - Chiara Rover, CR (Ciceroniana On Line)
This contribution suggests the hypothesis of a rather late dating, in the context of the Epicurean tradition, of the anti-sceptical dispute conducted by Lucretius in the fourth book of his poem (spec. vv. 469-521). To this end, some parallels between the Lucretian polemic and the position that Cicero, in the Lucullus, attributes to Lucullus, spokesman of Antiochus of Ascalon (135/130-68 BC), will be examined. The assonance between the  controversy conducted by Lucullus against academic scepticism and the arguments outlined in the fourth book of De rerum natura, together with the elements of Stoicism ascribed to Antiochus’ “syncretism”, testify to how Lucretius’ verses could be the result of a comparison with various “endemic” instances of the philosophical temperament of the years in which their author lived and wrote.